PENGARUH KOMPETENSI, MOTIVASI KERJA, DAN ETOS KERJA TERHADAP KINERJA BINTARA SANDI YUDHA GRUP 3 KOMANDO PASUKAN KHUSUS JAKARTA - Amirudin, Muhammad; Dirwan, Ahmad (Jurnal Ilmiah Manajemen SURYA PASCA SCIENTIA, 2024)
This study aims to analyze the effect of competence, work motivation,and work ethic on the performance of Bintara Sandi Yudha Group 3 of the JakartaSpecial Forces Command. This study uses a quantitative approach, survey methods and path analysis. The population is 60 people, with a saturated sampletechnique obtained 60 respondents. Data were analyzed using Excel and SPSSversion 25.00. The results showed that: Competence has a positive and significant direct effect on work ethic of 0.574; Work motivation has a positive andsignificant direct effect on work ethic of 0.285; Competence has a positive and significant direct effect on performance of 0.372; Work motivation has a positive and significant direct effect on performance of 0.332; Work ethic has a direct positive and significant effect on the performance of Bintara Bintara Sandi YudhaGroup 3 of the Jakarta Special Forces Command of 0.295. The implication is thatto improve the performance of Bintara Sandi Yudha Group 3, the Jakarta Special Forces Command needs to improve competence, work motivation, and work ethic.Keywords: Competency, work motivation, work ethic, performance